Analysis of Octopus Raw Material Inventory (Octopus sp) on the Production Process (Case Study: PT Kelola Mina Laut Makassar) - Ilham Ahmad; Andi Ridwan Makkulawu (International Journal of Economics, Business and Innovation Research, 2023)
Inventory is a company's wealth that has an important role in business operations, so companies need to carry out proactive management, meaning that companies must be able to anticipate conditions and challenges that exist in inventory management to achieve the ultimate goal, namely to minimize the total costs that must be incurred by the company for handling inventory. The production process is the process of processing raw materials into finished products or ready-to-use products. In a production process it is said to be efficient and effective if during the production process it does not produce many losses. The purpose of this study was to analyze the supply of octopus (Octopus sp) raw materials for the production process at PT Kelola Mina Laut Makassar. The results obtained by using ARIMA modeling, obtained the right model to describe the data analysis of octopus (Octopus Sp) raw material inventory at PT Kelola Mina Laut Makassar, namely the ARIMA model (0,1,1) with an MSE of 0.01927 and a MAPE of 16 .89%. ARIMA model (0,1,1), with the conclusion that raw material data for octopus at PT Kelola Mina Laut Makassar with data per week over a period of two years for forecasting the next 48 weeks has decreased.